DDA 기본골격에 대한 미국의 반응과 평가 - 김재수 (농림부, 2005)
ABSTRACT The WTO/DDA framework for agriculture agreed on August 1, 2004 is very important for all member countries including Korea, although much remains to be negotiated. The views of the U.S. remain important due to its role in the WTO negotiation. Their views will somewhat determine the understanding of the framework. The U.S. sees the framework as a significant achievement along with the farm groups in the U.S., especially in the export subsidy area which requires elimination of all forms of export subsidies. The Korean agricultural sector must also prepare by examining the framework carefully, while modifying strategies for future negotiations and general domestic agricultural programs. In addition, the Korean government must obtain developing country status in continuing its negotiation to receive more favorable treatment in the implementation process.
Keywords: 도하 개발 어젠다; 기본 골격; 국내보조; 시장접근; 수출 경쟁; Doha Development Agenda; framework; domestic support; market access; export competition